Targeting key angiogenic pathways with a bispecific CrossMAb optimized for neovascular eye diseases - Regula, Jörg Thomas; Koss, Michael Janusz (EMBO molecular medicine, 2016)
The ratio of angiopoietins ANG‐1 and ANG‐2 regulates vessel quiescence and neoangiogenesis as well as barrier function. It also acts as a switch from health to neovascular eye diseases.
Gesehen am 19.02.2021